The Efficiency of Cyperus rotindus Rhizomes Extract as Antibacterial Agents against some Pathogenic Bacteria - Al-Ghazali, Linda H.; Abed, Salam A.; Kadhim, Ayam R. A. (Scientific Journal of Medical Research, 2021)
Three extracts of Cyperus rotundus L. rhizomes were prepared in chloroform, ethyl acetate and ethanol, four pathogenic bacteria, including gram-negative (Enterobacter cloacae and Pseudomonas aeruginosa) and gram-positive (Staphylococcus aureus and Enterococcus faecalis) were used as tested microbes for evaluation of the extracts antibacterial activity by agar well diffusion method. The ethanolic extract showed the best antibacterial activity when compared with chloroform and ethyl acetate ones. Further, the inhibition activity of the extract was varied depending on the bacterial type, either gram-positive or negative, and the extract concentration used in each treatment. The rhizomes extracted by ethanol with the highest inhibition activity were further studied to investigate the minimum inhibitory concentration (MIC) against the four pathogenic bacteria species, so different concentrations were tested. viz., 16, 17, 18, and 19 mg/100 mL, and the results revealed that the concentrations 16, 17, and 18 were the Minimum inhibitory concentrations (MIC) values to S. aureus, E. faecalis, E. cloacae, and P. aeruginosa, respectively.